Bacillus Calmette-Guérin immunotherapy induces an efficient antitumor response to control murine melanoma depending on MyD88 signaling - Borges, Vinícius M.; Marinho, Fábio V.; Caldeira, Christiane V. A.; de Queiroz, Nina M. G. P.; Oliveira, Sergio C. (Frontiers in Immunology, 2024)
Bacillus Calmette-Guérin (BCG) is the first line treatment for bladder cancer and it is also proposed for melanoma immunotherapy. BCG modulates the tumor microenvironment (TME) inducing an antitumor effective response, but the immune mechanisms involved still poorly understood. The immune profile of B16-F10 murine melanoma cells was assessed by infecting these cells with BCG or stimulating them with agonists for different innate immune pathways such as TLRs, inflammasome, cGAS-STING and type I IFN. B16-F10 did not respond to any of those stimuli, except for type I IFN agonists, contrasting with bone marrow-derived macrophages (BMDMs) that showed high production of proinflammatory cytokines. Additionally, we confirmed that BCG is able to infect B16-F10, which in turn can activate macrophages and spleen cells from mice in co-culture experiments. Furthermore, we established a subcutaneous B16-F10 melanoma model for intratumoral BCG treatment and compared wild type mice to TLR2 -/-, TLR3 -/-, TLR4 -/-, TLR7 -/-, TLR3/7/9 -/-, caspase 1 -/-, caspase 11 -/-, IL-1R -/-, cGAS -/-, STING -/-, IFNAR -/-, MyD88 -/-deficient animals. These results in vivo demonstrate that MyD88 signaling is important for BCG immunotherapy to control melanoma in mice. Also, BCG fails to induce cytokine production in the co-culture experiments using B16-F10 and BMDMs or spleen cells derived from MyD88 -/-compared to wild-type (WT) animals. Immunotherapy with BCG was not able to induce the recruitment of inflammatory cells in the TME from MyD88 -/-mice, impairing tumor control and IFN-γ production by T cells. In conclusion, MyD88 impacts on both innate and adaptive responses to BCG leading to an efficient antitumor response against melanoma.